2019
DOI: 10.36487/acg_rep/1915_109_mcjannet
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation from coal mine pit lakes: measurements and modelling

Abstract: Open cut coal mines can have large surface water catchments and often extend to depths below the natural water table level with constant dewatering required to maintain coal extraction. When mining ceases, surface water runoff and groundwater start to fill the void, and pit lakes form. Understanding the hydrological and chemical evolution of these lakes is important for appropriate closure planning. One of the key processes controlling pit lake evolution is evaporation loss, and current estimates of this proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…As such, water evaporation in a floating pan more closely simulates lake evaporation. McJannet et al (2019) found success, however, with limitations, in using this method in a pit lake environment. When floating pan evaporation was modelled with meteorological data collected from a station sited on a pit rim, McJannet et al (2019) determined that estimated evaporation at the rim did not correctly simulate actual evaporation due to differences between meteorological conditions at the pit rim and at the lake water surface.…”
Section: Floating Pan Evaporationmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, water evaporation in a floating pan more closely simulates lake evaporation. McJannet et al (2019) found success, however, with limitations, in using this method in a pit lake environment. When floating pan evaporation was modelled with meteorological data collected from a station sited on a pit rim, McJannet et al (2019) determined that estimated evaporation at the rim did not correctly simulate actual evaporation due to differences between meteorological conditions at the pit rim and at the lake water surface.…”
Section: Floating Pan Evaporationmentioning
confidence: 99%
“…McJannet et al (2019) found success, however, with limitations, in using this method in a pit lake environment. When floating pan evaporation was modelled with meteorological data collected from a station sited on a pit rim, McJannet et al (2019) determined that estimated evaporation at the rim did not correctly simulate actual evaporation due to differences between meteorological conditions at the pit rim and at the lake water surface. However, when corrections were applied to the meteorological data collected at the pit rim to represent conditions at the surface water interface, the modelled evaporation provided accurate results.…”
Section: Floating Pan Evaporationmentioning
confidence: 99%
See 1 more Smart Citation
“…In estimating evaporation for pit lake water balance modelling, the common practice is to employ an empirical pan coefficient model, which assumes that lake evaporation is a constant proportion of pan evaporation measured at the nearest weather station [6]. In some cases, gridded climate products are applied that interpolate adjusted pan evaporation measurements [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the relation between lake evaporation and that measured at nearby evaporation pans can vary strongly between sites and over time for various reasons [8,9]. For a pit lake, shading of the water surface and sheltering from the wind by the pit walls and landscape around the pit can significantly reduce lake evaporation; while funneling of wind through an elongated pit can increase evaporation [5,6]. Very few pit lakes have in situ evaporation pans and, where these are present, they tend to be temporary and provide only 1-2 years of measurements.…”
Section: Introductionmentioning
confidence: 99%